Coexistance of celiac disease and type 1 diabetes - Szaflarska-Popławska, Anna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
There is a selective review of the literature concerning the coexistence of coeliac disease and type 1 diabetes mellitus. This review focuses on the principles of serological tests towards coeliac disease in patients with type 1 diabetes mellitus and metabolic control measures as a result of a gluten-free diet.